2020
DOI: 10.1016/j.jhazmat.2020.122037
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of cadmium and lead polluted soil using thiol-modified biochar

Abstract: Thiol-modified rice straw biochar (RS) was prepared by an esterification reaction with βmercaptoethanol and used for the remediation of Cd and Pb polluted soils. Modified biochar was characterized through elemental analysis, BET analysis, FE-SEM, FT-IR and XPS. These analyticalcharacterizations confirmed that the thiol groups were successfully grafted onto the surface of the biochar and were involved in the metal ion complexation. The batch sorption experiments showed that Cd 2+ and Pb 2+ sorption onto RS foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(58 citation statements)
references
References 92 publications
2
56
0
Order By: Relevance
“…The fitted kinetic model showed that all three sorbents were better described by the pseudo-second-order kinetic model with an R 2 value of 0.99, for both Cd and Pb ( Table 2 ). Fan et al reported that the sorption mechanism could differ based on a fitted sorption kinetic model [ 46 ]. When the sorption kinetic model was well fitted to the pseudo-first-order kinetic model, mononuclear sorption could be the main sorption mechanism, whereas chemical sorption could be the main sorption mechanism when pseudo-second-order sorption kinetics data were well fitted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fitted kinetic model showed that all three sorbents were better described by the pseudo-second-order kinetic model with an R 2 value of 0.99, for both Cd and Pb ( Table 2 ). Fan et al reported that the sorption mechanism could differ based on a fitted sorption kinetic model [ 46 ]. When the sorption kinetic model was well fitted to the pseudo-first-order kinetic model, mononuclear sorption could be the main sorption mechanism, whereas chemical sorption could be the main sorption mechanism when pseudo-second-order sorption kinetics data were well fitted.…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates that the Langmuir isotherm model was more suitable than the Freundlich model for describing the sorption of Cd and Pb using the sorption materials in this study. Fan et al (2020) noted that the Langmuir isotherm model could determine the sorbed compounds on the surface of sorption materials on the monolayer or equivalent sites, whereas the Freundlich isotherm model describes the adsorption process occurring on a heterogeneous surface [ 46 ]. Because a higher correlation coefficient was observed in the Langmuir isotherm model, Cd and Pb were sorbed on the homogeneous surface via monolayer sorption rather than heterogeneous surface sorption with ionic interaction [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 26 ] According to the IEs calculated from the decrease in Cd DTPA , TPAL exhibited a higher immobilization capacity compared to PAL, and this advantage was caused by the modification of the thiol group. Recently, some thiol‐functionalized materials, such as mercapto‐functionalized reactive nanosilica, [ 5 ] thiol‐modified biochar, [ 27–29 ] and sulfur‐modified wheat straw biochar, [ 30 ] have been prepared and applied as potentially effective amendments.…”
Section: Discussionmentioning
confidence: 99%
“…The pH and cation exchange capacity of the soil increases due to the addition of porous biochar which lead to Cd remediation. The remediation of Pb and Cd polluted soil was also performed using thoil-modified biochar and the maximum adsorption capacities recorded were 61.4 mg/g and 45.1 mg/g, respectively [61]. Addition of biochar into soil may indirectly remediate toxic metals via the enrichment of microorganisms that are capable of remediating toxic metals [62].…”
Section: Role Of Biochar In Pollution Managementmentioning
confidence: 99%